Nanoemulsions: formation, structure, and physical properties - T G Mason (2006)
We summarize procedures for producing ‘nanoemulsions’ comprised of nanoscale droplets, or ‘nanoemulsions’, methods for controlling the droplet size distribution and composition, and interesting physical properties of nanoemulsions. In contrast to more common microscale emulsions, nanoemulsions exhibit optical transparency at high droplet volume fractions, φ, surprisingly strong elasticity at low φ, and enhanced diffusive transport and shelf stability. For these reasons, nanoemulsions have great potential in a wide range of industries including pharmaceuticals, foods, and personal care products.